Effects of Astragalus polysaccharide supplementation on growth performance, carcass quality, muscle fiber characteristics, meat quality, and development of finishing pigs - Ma, Wenfeng; Ma, Zhuo; Zhang, Xiaoli; Mao, Pei; Gao, Mengmeng; Zhao, Lingping; Wu, Qiujue (Frontiers in Nutrition, 2025)
This study systematically evaluated the effects of Astragalus polysaccharides (AP) on growth performance, carcass quality, muscle fiber characteristics, and meat quality in finishing pigs. A total of 80 crossbred pigs (86.30 ± 1.0 kg) of approximately 5 months of age were selected and randomly assigned four treatments (five replicates for each treatment and four pigs for each replicate) on the basis of their initial body weight. They were, respectively, fed a basal diet (control group), and a basal diet supplemented with 0.1, 0.2%, or 0.3% AP. The results showed that compared with the control treatment, supplementation with Astragalus polysaccharides significantly increased the final body weight (FBW), average daily gain (ADG), and average daily feed intake (ADFI), and improved the dressing percentage, loin eye area, lean meat percentage, pH24h, a*, cooking percentage, marbling scores, and intramuscular fat (IMF) of carcass and meat (p < 0.05). In addition, the AP treatments also increased the contents of phenylalanine, methionine, and several other amino acids in the meat; growth serum hormone (INS, IGFs, and T3) concentrations; muscle fiber cross-sectional areas; and the mRNA expression levels of FBOX32 and MyoG in muscles (p < 0.05). Meanwhile, AP treatments also significantly decreased the feed-to-gain ratio (F/G), fat percentage, L*, b*, and shear force of meat, somatostatin (SS) and T4 serum concentrations, and muscle fiber diameters (p < 0.05). However, there were no significant differences in these parameters between the treatments with different levels of Astragalus polysaccharide supplementation these parameters (p > 0.05). In conclusion, this study demonstrates that the diet supplementation of Astragalus polysaccharides improves growth performance, carcass characteristics, and meat quality in finishing pigs. These improvements are evidenced by elevated altering amino acid compositions; optimized serum hormone concentrations related to growth; favorable muscle fiber characteristics; and upregulated the mRNA expression of key genes modulating muscle growth and development.